Hadith #2194 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
The Prophet (ﷺ) said: There are three things which, whether undertaken seriously or in jest, are treated as serious: Marriage, divorce and taking back a wife (after a divorce which is not final)
Grade: Hasan

Hadith #2281 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
Asma’, daughter of Yazid ibn as-Sakan al-Ansariyyah, was divorced in the time of the Messenger of Allah (ﷺ). No waiting period was prescribed for a divorced woman (at that time). When Asma’ was divorced, Allah, the Exalted, sent down the injunction of waiting period for divorce. She is the first of the divorced women about whom the verse relating to waiting period was sent down.
Grade: Hasan

Hadith #2312 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
Mu’tamir reported on the authority of his father Sa’id bin Al Hassan explain the Qur’anic verse “But if anyone compels them, yet after such compulsion is Allaah oft-forgiving most merciful(to them), said Allaah is oft-forgiving to those (slave girls) who were compelled (to prostitution)
Grade: Da'if

Hadith #2315 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
Salamah bin Al Akwa said “After the revelation of the verse “For those who can do it(with hardship) is a ransom, the feeding of one, that is indigent, is one of us intended to leave fast and pay ransom, he could do so.” until the verse following it was revealed and abrogated the (previous) verse.”
Grade: Sahih

Hadith #2469 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Ma'mar bin Rashid معمر بن راشد; Safiyya bint Shayba bin 'Uthman (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to observe I’tikaf in the mosque and put his head near me through the opening of the apartment, and I would wash his head. Musaddad said: “And I would comb it while I was menstruating.”
Grade: Sahih

Hadith #2504 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
The Prophet (ﷺ) said: Use your property, your persons any your tongues in striving against the polytheists.
Grade: Sahih

Hadith #2571 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib (Sunan Abi Dawud)
Anas reported the Apostle of Allaah(ﷺ) as saying “Keep to travelling by night, for the earth is traversed (more easily) by night.
Grade: Sahih

Hadith #2770 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
‘Abd Allah bin ‘Umar said “When the Apostle of Allaah(ﷺ) returned from an expedition, Hajj or ‘Umrah on every rising piece of ground he would say three times “Allaah is Most Great” and he would say “There is no god bt Allaah alone who has no partner, to Whom the dominion belongs, to Whom praise is due, and Who is Omnipotent, serving, prostrating ourselves before our Lord and expressing praise. Allaah alone has kept his word, helped His servant and routed the confederate.
Grade: Sahih

Hadith #2816 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
I entered upon al-Hakam b. Ayyub along with Anas. He saw some youths or boys who had set up a hen and shooting at it. Anas said: The Messenger of Allah (ﷺ) forbade to kill an animal in confinement.
Grade: Sahih

Hadith #2842 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib (Sunan Abi Dawud)
On his father’s authority, said that his grandfather that the Messenger of Allah (ﷺ) was asked about the aqiqah. He replied: Allah does not like the breaking of ties (uquq), as though he disliked the name. And he said: If anyone has a child born to him and wishes to offer a sacrifice on its behalf, he may offer two resembling sheep for a boy and one for a girl. And he was asked about fara’. He replied: Fara’ is right. If you leave it (i.e. let it grow till it becomes a healthy camel of
Grade: Hasan

Hadith #2868 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said to me: Abu Dharr, I see you weak, and I like for you what I like for myself. Do not be a leader of two (persons), and do not be a guardian of an orphan. Abu Dawud said: This has been narrated only by the people of Egypt.
Grade: Sahih

Hadith #2908 - Sunan Abi Dawud - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Amr bin 'Uthman عمرو بن عثمان بن عفان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Usamah ibn Zayd (Sunan Abi Dawud)
On his father’s authority, said that his grandfather reported from the Prophet (ﷺ) something similar.
Grade: Sahih

Hadith #2920 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
The Prophet (ﷺ) said: When an infant has raised its voice (and then dies), it will be treated as an heir.
Grade: Sahih

Hadith #2923 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
I used to learn the reading of the Qur’an from Umm Sa’d, daughter of al-Rabi’. She was an orphan in the guardianship of Abu Bakr. I read the Qur’anic verse “To those also to whom your right hand was pledged.” She said: Do not read the verse; “To those also to whom your right hand was pledged.” This was revealed about Abu Bakr and his son ‘Abd al-Rahman when he refused to accept Islam. Abu Bakr took an oath that he would not give him a share from inheritance. When he embraced Is
Grade: Da'if

Hadith #2985 - Sunan Abi Dawud - Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Ali ibn Abi Talib; Anbs'h bin Khalid bin Yazid عنبسة بن خالد بن يزيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
AbdulMuttalib ibn Rabi’ah ibn al-Harith said that his father, Rabi’ah ibn al-Harith, and Abbas ibn al-Muttalib said to AbdulMuttalib ibn Rabi’ah and al-Fadl ibn Abbas: Go to the Messenger of Allah (ﷺ) and tell him: Messenger of Allah, we are now of age as you see, and we wish to marry. Messenger of Allah, you are the kindest of the people and the most skilled in matchmaking. Our fathers have nothing with which to pay our dower. So appoint us collector of sadaqah (zakat), Messenger of All
Grade: Sahih

Hadith #2988 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
Ibn A’bud said, ‘Ali said to me “May I not narrate you about me and Fathimah daughter of the Apostle of Allaah(ﷺ)? She was most favorite to him of his family.” I said “Yes”. He said “She pulled the grinding stone with her hand so much that it affected her hand, she carried water in a water bag so much so that it affected the upper portion of her chest, she swept the house so much so that her clothes became dirty. The Prophet (ﷺ) acquired some slaves”. So I said “Would that
Grade: Da'if

Hadith #3589 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: A judge should not decide between the two while he is in anger.
Grade: Sahih

Hadith #3597 - Sunan Abi Dawud - Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Asim bin Muhammad bin Zayd عاصم بن محمد بن زيد العمري; ibn Umar; Matr bin Tahman al-Waraq مطر بن طهمان الوراق أبو رجاء الخراساني; Nafie' نافع مولى ابن عمر; Umar bin Yonus bin al-Qasim عمر بن يونس بن القاسم (Sunan Abi Dawud)
We were sitting waiting for Abdullah ibn Umar who came out to us and sat. He then said: I heard the Messenger of Allah (ﷺ) as saying: If anyone’s intercession intervenes as an obstacle to one of the punishments prescribed by Allah, he has opposed Allah; if anyone disputes knowingly about something which is false, he remains in the displeasure of Allah till he desists, and if anyone makes an untruthful accusation against a Muslim, he will be made by Allah to dwell in the corrupt fluid flowing
Grade: Sahih

Hadith #3671 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
A man of the Ansar called him and AbdurRahman ibn Awf and supplied them wine before it was prohibited. Ali then led them in the evening prayer, and he recited; “Say: O ye who reject faith.” He was confused in it. Then the following verse came down: “O ye who believe! approach not prayers with a mind befogged until you can understand all that ye say.
Grade: Sahih

Hadith #4370 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) cut off (the hands and feet of) those who had stolen his camels and he had their eyes put out by fire (heated nails), Allah reprimanded him on that (action), and Allah, the Exalted, revealed: “The punishment of those who wage war against Allah and His Apostle and strive with might and main for mischief through the land is execution or crucifixion.”
Grade: Da'if

Hadith #4411 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
We asked Fadalah b. ‘Ubaid about the hanging the (amputated) hand on the neck of a thief whether it was a sunnan. He said: A thief was brought to the Messenger of Allah (ﷺ) and his hand was cut off. Thereafter he commanded for it, and it was hung on his neck.
Grade: Da'if

Hadith #4736 - Sunan Abi Dawud - Ahmed bin Abi Sarayj أحمد بن أبي سريج; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Ali bin Muslim bin Sa'id علي بن مسلم بن سعيد الطوسي; ibn Mas'ud; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Muslim bin Sabih al-Hamdani, Abu al-Daha مسلم بن صبيح أبو الضحى; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
I was with the Negus when his son recited a verse of the Gospel. So I laughed. Thereupon he said : Do you laugh at the word of Allah, the Exalted?
Grade: Sahih

Hadith #4992 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Ma'mar bin Rashid معمر بن راشد; Safiyya bint Shayba bin 'Uthman (Sunan Abi Dawud)
The Prophet (ﷺ) said: It is enough falsehood for a man to relate everything he hears. Abu Dawud said: Hafs did not mention Abu Hurairah (in his version). Abu Dawud said: No other transmitter except this old man, that is, ‘Ali b. Hafs al-Mada’ini related the perfect chain of this tradition.
Grade: Sahih

Hadith #5014 - Sunan Abi Dawud - Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib; ibn Abbas; Ikrama عكرمة; Yazid bin Abi Sa'id يزيد بن أبي سعيد النحوي أبو الحسن (Sunan Abi Dawud)
so he (‘Umar’) feared that he would refer to the Messenger of Allah (May peace be upon him); therefore he allowed him.
Grade: Sahih

Hadith #5240 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; Ali bin al-Husain bin 'Ali علي بن الحسين بن علي - زين العابدين; Hussain ibn 'Ali ibn Abi Talib (Sunan Abi Dawud)
A similar report (as previous) was narrated from a man from Thaqif, from ‘Urwah bin Az-Zubair, who attributed the Hadith to the Prophet (ﷺ).
Grade: Sahih